From Imitation of Reality to Fantastic Game: Evolution of the Image of War in the Visual Arts - Foortai, Francisca (International Journal of Culture and History, 2023)
The article is devoted to analyze the starting point of the evolution of military subjects in the visual arts of antiquity and the images that it came to in modern cinema. From the author’s point of view, in the development of the image of war from the statement of war scenes in real life to fantastic games with machine warriors in the space of hyperreality, a crucial role was played not only by the impact of the historical era and the change of worldview, but also by the specifics of cinema as an art form, which perceived the theme of war as one of the archetypal artistic subjects. The article proposes to change the morphological status of cinema as the eighth art form and consider it as a threefold art in its Genesis, with the leading principles being man and machine, and nature (for the first time!) in the process of creating an artistic image, it appears as an auxiliary element. Due to its ontological specificity, cinema has special imaginative and artistic tools that create new images of war that are impossible in other visual arts.